Investigating EFL Learners’ Perceptions towards the Difficulties in Oral Presentation at Kandahar University - Tareen, Hashmatullah (European Scientific Journal, ESJ, 2022)
This research paper examined the difficulties of oral presentation, strategies coping with difficulties used in oral presentations and the perceived role of lecturer in improving EFL learners’ oral presentation skills. With regard to achieving these objectives, questionnaires distributed to 150 EFL learners, and face-to-face interviews were conducted. The quantitative data were analyzed through SPSS by conducting percentages, independent sample t-test and ANOVA tests. The results of the study revealed that learners had a problem with oral fluency, accuracy and pronunciation during oral presentation, feel frightened when a lot of people are watching them, afraid of being assessed by their classmates in front of the class, having low self-confidence. The results also revealed some strategies coping with difficulties used in oral presentation such as, learners have to prepare themselves properly before an oral presentation. Furthermore, considering a crucial role of lecturer in improving oral presentation skills, lecturer has to show learners videos of good speakers for enhancing their presentation skill and lecturer has to give learners freedom to choose their own topic that lowers their anxiety were discovered for more consideration. It is hoped that the ideas discussed will provide the learners and lecturers with basic guidelines of how to improve the learners’ oral presentation and assist the learners to work their way out of anxiety.